A Qualitative Study Exploring the Job Expectations of International Postgraduate Students Regarding Their Ideal Workplace. - Ali, Aaima (2020)
International students constitute a large part of the UK’s workforce. Those who move to this country for a postgraduate degree, end up wanting to find long term jobs and settlement for a better future for themselves, as well as their current or future families. While looking for these jobs, there are certain expectations that they have from their future employers, this is one part of the unsaid and unwritten, psychological contract between an employee and employer. It is imperative to dig deeper into what these expectations are, and how they can be catered to. Creating value for employees is something that employers need to do in order to create productive and meaningful workplaces. This study has used the qualitative method of research and analysis to conduct open ended interviews of international postgraduate students. A thematic analysis has been used to scrutinise the findings and draw a comparison of the themes discovered, with previous research and theories of job expectations. It was found that the top most priority by postgraduates, is given to financial rewards, flexibility, and an open culture, when looking for their ideal workplaces. It was also found that while the themes identified were much in line with past researches, there were no gender differences for this cohort selected, in the preferences laid out.